A case of Henoch-Schonlein Purpura with dilated coronary arteries - Jessica L. Bloom; Jeffrey R. Darst; Lori Prok; Jennifer B. Soep (Pediatric Rheumatology Online Journal, 2018)
Abstract Background Henoch-Schonlein Purpura (HSP) is one of the most common vasculitides of childhood, with 10–20 cases per 100,000 children. It frequently occurs following an infectious trigger and involves IgA and C3 deposition in small vessel walls. HSP is characterized by palpable purpura plus IgA deposition on biopsy, arthritis/arthralgia, renal involvement (hematuria and/or proteinuria), and/or abdominal pain. It is not generally recognized as a cause of dilated coronary arteries. Case presentation We describe the first reported case of HSP presenting with dilated coronary arteries. This patient is a nine-year-old previously healthy Caucasian male who presented with 1 week of petechiae on his lower legs, knee and ankle arthritis, and abdominal pain without fever, consistent with HSP. An echocardiogram revealed coronary dilation, including the left main (5.32 mm, Z score + 4.25) and left anterior descending (LAD) (3.51 mm, Z score + 2.64) coronary arteries. He received high dose aspirin, IVIG, and infliximab with normalization of the LAD. Skin biopsy revealed leukocytoclastic vasculitis with positive IgA staining. He was Rhinovirus/Enterovirus positive with Group A Streptococcus on throat culture. Conclusion Cardiac findings, while rare, can exist in HSP. Coronary dilation appeared to respond to our hospital protocol’s Kawasaki Disease (KD) therapy, possibly indicating an overlap in HSP and KD pathophysiology. This case, along with prior reports of dilated coronaries in systemic juvenile idiopathic arthritis (SJIA), highlights the importance of considering other sources of systemic inflammation, in addition to KD, when coronary dilation is identified. The appropriate therapy, follow-up, and prognosis for our patient are not clear, as further studies are needed to determine the natural course of these findings.